1994
DOI: 10.1128/mcb.14.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a Saccharomyces cerevisiae peptide transport gene.

Abstract: We have cloned and characterized a Saccharomyces cerevisiae peptide transport gene (PTR2) isolated from a genomic DNA library by directly selecting for functional complementation of a peptide transport-deficient mutant. Deletion and frameshift mutageneses were used to localize the complementing activity to a 3.1-kbp region on the transforming plasmid. DNA sequencing of the complementing region identified an open reading frame spanning 1,803 bp. The deduced amino acid sequence predicts a hydrophobic peptide con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(135 citation statements)
references
References 68 publications
4
130
0
Order By: Relevance
“…So far no data are available as to whether CHLl or the peptide transporters also transport histidine. Expression of these proteins in JT16 and expression of NTRl and CHLl in the yeast peptide transport mutant or expression in oocytes, as shown for the rabbit oligopeptide transporter, may be tools to study the inter-relationship of the transport activities of the three types of transporters [4,21,24]. Due to the comparable sequence similarities of the different transporters, the comparison did not help in defining the actual function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far no data are available as to whether CHLl or the peptide transporters also transport histidine. Expression of these proteins in JT16 and expression of NTRl and CHLl in the yeast peptide transport mutant or expression in oocytes, as shown for the rabbit oligopeptide transporter, may be tools to study the inter-relationship of the transport activities of the three types of transporters [4,21,24]. Due to the comparable sequence similarities of the different transporters, the comparison did not help in defining the actual function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore new genes could be identified that mediate growth of JT16 on media containing 6 mM histidine and that also encode integral membrane proteins. The gene described in this manuscript is a typical membrane protein with 12 putative membrane spanning regions and is homologous to two other types of transporters, namely the low affiity nitrate transporter from Arabidopsis and peptide transporters from yeast and mammalian origin [4,21,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of a Saccharomyces cerevisiae peptide transport mutant (ptr2) facilitated the cloning of a yeast peptide transporter by functional complementation (Perry et al, 1994). Complementation of the ptr2 mutant with an Arabidopsis thaliana cDNA library subsequently resulted in the isolation of a root-specific di-and tripeptide transporter AtPTR2-A .…”
Section: Introductionmentioning
confidence: 99%
“…Initial peptide uptake rates were observed to be higher in cells that were grown on poor nitrogen sources, such as proline, than in cells grown on preferred nitrogenous materials, such as glutamine. Based on this criterion, it has been proposed that the peptide transport system of yeasts falls under the regulatory control of the nitrogen catabolite repression mechanism 18 . Probably a similar inactivation as happens in the GAP1 system, may take place for the peptide transport system, when yeast cells have been propagated in a medium with ammonium ions as the sole nitrogen source.…”
Section: Introductionmentioning
confidence: 99%